Exploring the mediating effect of business analytics on the relationship between crisis management and digital marketing practices - Al-Suhimat, Saed; htibat, Ameen Al; Awamleh, Fawwaz Tawfiq (International Journal of Innovative Research and Scientific Studies, 2025)
This research examines the mediating function of business analytics between crisis management and digital marketing practices in 25 Jordanian mid-sized companies. The main aim is to examine the extent to which data-based knowledge can contribute to the responsiveness of marketing during organizational crises. Employing a quantitative method, 401 usable responses were obtained from risk management experts and marketing managers. Statistics were tested via Smart PLS 4 for structural relationship testing. The results indicate that crisis management has a significant impact on digital marketing performance, and the impact is further enhanced through the incorporation of business analytics into practice. The findings highlight the importance of infusing analytical competence into organizational strategy to facilitate timely and knowledge-based decision-making in times of crisis. The research adds to the body of literature by presenting an integrated model that brings together the conceptually distinct fields of crisis management and marketing and, through analysis, illustrates how their convergence can increase organizational resilience. The research provides, in practice, managerial recommendations for optimizing marketing performance during crises through business analytics-based strategic actions and resource allocation.